(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
We must build our future on a solid foundation. And this basis is patriotism. No matter how long we discuss things that can be the foundation, the strong moral foundation for our country, we still cannot think of anything else. It is a tribute to our history and traditions, the spiritual values of our peoples, our thousand-year-old culture and the unique experience of the coexistence of hundreds of peoples and languages on the territory of our country. It is a responsibility for your country and its future.